From pigs to incineration and beyond: The evolution of organic waste and food management in Sweden in the period 1800 – 2000 and future prospects - Jan-Olof Drangert; Jonas Hallström (City and Environment Interactions, 2023)
Societies have always been occupied with securing food supply and ensure environmental and human health. Scientific knowledge and technical level have, together with habitat and management patterns, shaped sanitation arrangements and recycling of resources. Because it is the same urban problems that are addressed by societies in different historical contexts, a longitudinal study may allow for novel ways to conjure food security and sanitation management issues in the present century.We trace the historical transition over two centuries away from a circular economy to a more linear one in two Swedish cities, the capital Stockholm and the industrial city Norrköping, and show that big but rather slow changes occurred more or less constantly in these two urban settings. The driving forces have changed from only improving local conditions of sanitation and food production over to global and regional driving forces in this century affecting what local communities can or could do. The ongoing globalization positions the subjects of environmental and human health, recycling and food security in a new global perspective, where climate change and global resource boundaries will play a central role. We cannot continue to rely on trade that causes rainforest destruction elsewhere or harmful chemical consumer products that lead to loss of biodiversity and human health risks.We need to put urban sanitation and food issues into this wider perspective with available remedial measures such as dietary changes, food waste reduction, soil less food production and building of new circular infrastructure. All urban areas in the world, including Stockholm and Norrköping in Sweden, need to adopt new strategies that again engage residents as well as public sectors and industry, including agriculture.